2022
DOI: 10.1212/cpj.0000000000001172
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hypertension in a Transgender Man

Abstract: ObjectiveCase description of recurrent idiopathic intracranial hypertension (IIH) in a transgender man on gender-affirming hormone therapy.MethodsCase report.ResultsA 24-year-old transmasculine patient (assigned female at birth), with a body mass index (BMI) of 37.3, presented with headaches, transient visual obscurations (TVOs), pulsatile tinnitus, Frisén 5 papilledema, and scotomas. He was diagnosed with IIH after normal magnetic resonance imaging (MRI) and magnetic resonance venogram (MRV), an elevated open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…More than 70% of the reviewed studies were focused on neurological sequelae of human immunodeficiency virus (HIV). Since that time, there has been progress, with studies published related to movement disorders, 16,17 multiple sclerosis, 18 stroke, 13,19 headache, 8,20 sleep, 21 and cognitive disorders. [22][23][24] Neurology research on intersex individuals is limited.…”
Section: Paucity Of Studies Incorporating Sexual Orientation Gender I...mentioning
confidence: 99%
“…More than 70% of the reviewed studies were focused on neurological sequelae of human immunodeficiency virus (HIV). Since that time, there has been progress, with studies published related to movement disorders, 16,17 multiple sclerosis, 18 stroke, 13,19 headache, 8,20 sleep, 21 and cognitive disorders. [22][23][24] Neurology research on intersex individuals is limited.…”
Section: Paucity Of Studies Incorporating Sexual Orientation Gender I...mentioning
confidence: 99%
“…In this issue of Neurology® Clinical Practice , Qureshi et al 1 present a case of a transgender man of childbearing age with a reported body mass index of 37 who presents with idiopathic intracranial hypertension (IIH). The authors conclude that exogenous testosterone as part of a gender-affirming hormone regimen may be a potential mechanism for his diagnosis of IIH, based on prior evidence that disorders in androgen metabolism may influence CSF production.…”
mentioning
confidence: 99%